A lotus root-like appearance in a spontaneously recanalized lesion confirmed by serial coronary angiography: from optical coherence tomography study. Issue 2 (March 2019) - Dai, Kazuoki; Suruga, Kazuki; Nakano, Takayuki; Takemoto, Hajime; Hashimoto, Yu; Tomomori, Syunsuke; Higaki, Tadanao; Oi, Kuniomi; Kawase, Tomoharu; Nakama, Yasuharu; Suenari, Kazuyoshi; Nishioka, Kenji; et al.
Abstract : Supplemental Digital Content is available in the text.